A novel high-throughput neutralization assay for supporting clinical evaluations of human cytomegalovirus vaccines - Tang, Aimin; Li, Fengsheng; Freed, Daniel C.; Finnefrock, Adam C.; Casimiro, Danilo R.; Wang, Dai; Fu, Tong-Ming (Vaccine, 2011)
► We developed a neutralizing assay for measuring antiviral activity against CMV. ► This assay format is no longer relying on virus induced cytopathic effect and can be easily adapted to high throughput format. ► We demonstrated its utility to support clinical and vaccine studies. Neutralizing antibodies are considered an important component of protective immunity against congenital infection of human cytomegalovirus (HCMV), a frequently cited cause of birth defects. An effective HCMV vaccine is desired to induce potent neutralizing antibodies in seronegative females, so that the viral transmission to fetus would be blocked if the women contracted HCMV infections during their pregnancies. We describe a novel microneutralization assay to measure antiviral activities against HCMV in serum samples. The assay is based on detection of a dominant HCMV antigen expressed in cells, using near infrared dye-labeled immune reagents. Since the detection is independent of viral cytopathic effects, this assay format has the appeal of a short turn-around time and a read-out that is not subject to operator experience and judgment, making it a promising platform to support large scale clinical studies. In a serological survey of a cohort of 200 healthy females, we showed that the neutralizing titers measured in this assay are highly comparable to those from a neutralization assay based on an enzyme-linked immunostaining method. Lastly, to demonstrate the utility of this assay to support HCMV vaccine study, we presented the results of neutralizing titers from a rhesus macaque vaccination study.